Baptism as Christian initiation according to the Catechism for Filipino Catholics pedagogical implications for today - Asis, Michael Demetrius H. (Perspective in the Arts and Humanities ASIA (formerly Asian Perspectives in the Arts and Humanities), 2016)
Given the prevailing outlook today that baptism automatically washes away sin if the rite is correctly administered, there are five topics that need to be highlighted and explained in any prebaptismal instruction or catechesis. These are : (1) Christ's baptism as confirmation of his identity and call to inaugurate the Kingdom of God; (2) Christ as the truly "baptized one," who is "deeply immersed" in God, including an explanation of how this idea is actually replicated and lived out in the faith of the family who represents the child in infant baptisms; (3) the refocusing from water washing away original sin to the Holy Spirit freeing us from sin; water's life sustaining and destructive qualities which symbolize Christ's passage from death to life, and our own participation in this paschal mystery; (5) baptism into Christ as baptism into his body, the Church, since the struggle with our individual sins and the sins of the world is always a collective task, in view and in fulfillment of Christ's threefold mission as prophet, priest and king, to further God's reign in the world. These topics highlight the fact that baptism, like any other sacrament, works not only through the intrinsic power of the sacraments to communicate grace, but more importantly, through the active and intentional engagement in faith and holiness of both recipients and ministers, an engagement which makes the sacraments not only canonically valid but existentially fruitful and effective.